Outcomes of surgical aortic valve replacement for mixed aortic valve disease - Philip, Jennifer L.; Zens, Tiffany; Lozonschi, Lucian; De Oliveira, Nilto C.; Osaki, Satoru; Kohmoto, Takushi; Akhter, Shahab A.; Tang, Paul C. (Journal of Thoracic Disease, 2018)
Background: Mixed aortic valve disease (MAVD) is associated with a poorer natural history compared with isolated lesions. However, clinical and echocardiographic outcomes for aortic valve replacement (AVR) in mixed disease are less well understood. Methods: Retrospective review of AVRs (n=1,011) from 2000–2016. Isolated AVR, AVR + coronary bypass, and AVR + limited ascending aortic replacement were included. Predominant aortic stenosis (AS) group was stratified into group 1 (n=660) with concomitant mild or less aortic insufficiency (AI), and group 2 (n=197) with accompanying moderate or greater AI. Predominant AI group was stratified using the same schema for concomitant AS into groups 3 (n=143) and 4 (n=53). Median follow-up was 3.1 and 4.4 years respectively for AS and AI groups. Results: For the predominant AS group (n=857) preoperatively, group 2 had a larger preoperative left ventricular end diastolic diameter (LVESD) (51.0±8.4 vs. 48.6±7.2, P=0.02) and lower preoperative left ventricular ejection fraction (LVEF) (57.6% vs. 60.2%, P=0.043). No differences in left ventricular (LV) dimensions, LV or right ventricular (RV) function was evident at follow up (P>0.05). After propensity matching for age, operation, and comorbidities, there was no difference in survival (P=0.19). After propensity matching for the predominant AI group (n=196), survival was lower for group 4 compared to 3 (P=0.02). There were no differences in LV dimensions, LV or RV function preoperatively or on follow-up (P>0.05). Conclusions: Predominant AS associated with higher AI grades had larger LV dimensions and worse LV function preoperatively. These differences resolve after AVR with equivalent survival. However, predominant AI with more severe AS had reduced survival despite AVR.